Frequency Diverse Array SAR With Fast-Time Space-Time Adaptive Processing for Subsurface Imaging - Wen-Qin Wang (IEEE Access, 2023)
Different from the ground penetration radar providing only one-dimensional image, synthetic aperture radar (SAR) can produce two-dimensional and even three-dimensional image, which is meaningful in subsurface imaging, but possible layover effects may be a problem. Moreover, multipath reflections from the ground known as hot clutter or terrain scattered interferences will add nonstationary interference components to the subsurface imaging. In this paper, we present the use of fast-time space-time adaptive processing (STAP) to suppress undesired interferences for SAR subsurface imaging. Moreover, the frequency diverse array (FDA) range- and time-dependent beampattern is explored to enhance the SAR azimuth resolution and reduce fluctuations in the received signals, which helps in mitigating multipath effects and potentially addressing layover issues. The FDA-SAR platform moves at a constant speed along with the azimuth direction above the ground with a side-looking FDA antenna to formulate a strip-map side-looking SAR for subsurface imaging, where the FDA antenna elements also are placed along with the moving track of FDA-SAR platform. The research progress is reviewed and the most recent advances are introduced. The technical challenges and future works also are discussed. We aim to introduce the promising FDA-SAR with fast-time STAP for subsurface imaging and encourage further exploration in this domain.